APLICAÇÃO DA MODELAGEM MATEMÁTICA NA PRODUÇÃO DE CULTIVARES DE AVEIA BRANCA - Silva, José A. G. d.; Sausen, Airam T. Z. R.; Pinto, Fernando B.; Ubessi, Cassiane; Costa, Juliane S. P.; Mantai, Rubia D. (Salão do Conhecimento, 2013)
Resumo